2013
DOI: 10.1136/heartjnl-2012-302945
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting balloon angioplasty for in-stent restenosis: a systematic review and meta-analysis of randomised controlled trials

Abstract: In-stent restenosis is the bane of coronary angioplasty, and drug-eluting balloon angioplasty is a promising treatment option in this situation. It reduces the risk for MACE compared with plain balloon angioplasty or implantation of a Taxus Liberte drug-eluting stent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(56 citation statements)
references
References 36 publications
2
54
0
Order By: Relevance
“…A meta-analysis of trials using PEB for the treatment of BMS or DES ISR showed a significant reduction in the risk of occurrence of MACE (P<0.001), TLR (P=0.006), and the recurrence of binary in-segment restenosis (P<0.001) in the group with PEB compared with an inhomogeneous control group (POBA, PES). 22 Similarly, Gao et al 23 found that the treatment of ISR with PEB significantly reduced MACE (P<0.01), death (P=0.04), TLR (P<0.01), and LLL (P<0.01) compared with POBA; however, the differences were not significant when compared with DES (PES/EES).…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of trials using PEB for the treatment of BMS or DES ISR showed a significant reduction in the risk of occurrence of MACE (P<0.001), TLR (P=0.006), and the recurrence of binary in-segment restenosis (P<0.001) in the group with PEB compared with an inhomogeneous control group (POBA, PES). 22 Similarly, Gao et al 23 found that the treatment of ISR with PEB significantly reduced MACE (P<0.01), death (P=0.04), TLR (P<0.01), and LLL (P<0.01) compared with POBA; however, the differences were not significant when compared with DES (PES/EES).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, DCB compared to DES show a significant benefit in the treatment of ISR,5, 6, 7, 8, 9, 10, 11, 12 and current guidelines recommend the use of DCB for patients with coronary ISR (class I, level of evidence A) 13. However, there are other potential indications such as coronary small vessel disease and bifurcation lesions 14, 15.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Recently, 2 network meta-analyses were conducted comparing >2 treatments for ISR. Piccolo et al 33 compared treatments for DES-ISR using 8 randomized trials and did not account for unequal duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%